PENGARUH PERTUMBUHAN DANA PIHAK KETIGA DAN AKTIVA PRODUKTIF TERHADAP PERTUMBUHAN NET INTEREST MARGIN (NIM) PADA BANK-BANK PEMERINTAH DAERAH - Khuryatul Machila; Anggraeni Anggraeni (STIE Perbanas Surabaya, 2013)
This study attempts to solve the problem dealing with a good profitability of bank which occurs when net interest margin (NIM) on bank rises from year to year. However, this does not occur in the local government banks. Therefore, it is very important to find out what factors are influencing the decrease of NIM in local government banks. The aim of this study to determine the influence of demand deposits, saving deposits, time deposits, loan received, interbank placement, securities and loans both simultaneously and individually have significant effect on the NIM growth in local government banks. It uses multiple regressions for the analysis. It shows that demand deposits, saving deposits, time deposits, loan received, interbank placement, securities and loans growth simultaneously did not significantly affect the NIM growth in local government banks. Demand deposits, saving deposits, time deposits, interbank placement, loan received and loans growth partially did not affect insignificantly and negatively either. The security growth partially has significant and positive effect on the NIM and among seven independent variables; security growth has dominant effect on the NIM.